2002
DOI: 10.1042/bj20020186
|View full text |Cite
|
Sign up to set email alerts
|

Identification of the two essential groups in the family 3 β-glucosidase from Flavobacterium meningosepticum by labelling and tandem mass spectrometric analysis

Abstract: beta-Glucosidase from Flavobacterium meningosepticum (Fbgl) catalyses the hydrolysis of beta-1,4-glucosidic bonds via a two-step double-displacement mechanism in which two amino acid residues act as nucleophile and acid/base catalyst. Definitive identification of these two residues is provided by the two active-site-directed inactivators, 2',4'-dinitrophenyl-2-deoxy-2-fluoro-beta-d-glucoside (2FDNPG) and N-bromoacetyl-beta-d-glucosylamine (NBGN), which stoichiometrically label the nucleophile and the acid/base… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

3
28
0

Year Published

2002
2002
2017
2017

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 34 publications
(31 citation statements)
references
References 38 publications
3
28
0
Order By: Relevance
“…The activity of the Asp2863Ala mutation was too low for the K m to be accurately determined; thus, the apparent k cat was estimated. The decrease in the catalytic activity of this mutant of approximately 4 to 5 orders of magnitude (Table 3) coupled with the observation that this residue aligns with previously identified catalytic nucleophilic residues in GH3 enzymes (2,9,11,31,34,35,40) provides support for the assignment of Asp286 as the catalytic nucleophile for Xyl3B.…”
Section: Discussionsupporting
confidence: 80%
See 1 more Smart Citation
“…The activity of the Asp2863Ala mutation was too low for the K m to be accurately determined; thus, the apparent k cat was estimated. The decrease in the catalytic activity of this mutant of approximately 4 to 5 orders of magnitude (Table 3) coupled with the observation that this residue aligns with previously identified catalytic nucleophilic residues in GH3 enzymes (2,9,11,31,34,35,40) provides support for the assignment of Asp286 as the catalytic nucleophile for Xyl3B.…”
Section: Discussionsupporting
confidence: 80%
“…The catalytic nucleophile in several GH family 3 ␤-D-glucosidases has been identified by covalent labeling followed by mass spectrometry (2, 9, 11) and X-ray crystallography (30). The catalytic acid/ base that serves to protonate the leaving-group oxygen and subsequently activate an attacking water has been identified for several GH3 ␤-D-glucosidases (9,35,40). In addition to these two critical residues, GH3 enzymes possess three additional highly conserved amino acid residues (Arg, Lys, and His) that are predicted to be involved in catalysis (27,29).…”
mentioning
confidence: 99%
“…The domain A contains an essential Asp residue, the catalytic nucleophile [Dan et al, 2000;Li et al, 2001]. While there are some experimental evidences on the key role of the B domain [Chir et al, 2002], none of the residues is strictly conserved among the family-3 B domains. Some enzymes show a modified B domain that was named B) [Faure et al, 1999;Vroemen et al, 1995].…”
Section: Introductionmentioning
confidence: 99%
“…Detailed structural and mechanistic studies on several GH3 glycosidases have confirmed that both the ␤-glucosidases and the N-acetylglucosaminidases follow this mechanism (5)(6)(7)(8)(9)(10)(11)(12)(13). This contrasts sharply with the ␤-hexosaminidases from CAZy family GH20, which lack an enzymatic nucleophile and instead use the acetamide of the substrate in that role, forming an oxazoline or oxazolinium ion intermediate (14,15).…”
mentioning
confidence: 99%